Development Of A Virtual Anywhere Desktop Infrastructure (ADI) Computer Laboratory Model At Higher Education Institutions - Syamsu, Suryadi; Sapto Haryoko; Abdul Muis Mappalotteng (International Journal of Education, Vocational and Social Science, 2025)
Anywhere Desktop Infrastructure (ADI)-based virtual computer laboratory is designed to overcome the limitations of physical laboratories in higher education, such as space, cost, and accessibility constraints. This research aims to develop a valid, practical, and effective ADI-based laboratory model to support practicum learning in higher education. The research method used is Research and Development (R&D) by integrating the ADDIE, Borg and Gall, and Jerrold Kemp models. This research involved students and lecturers from the Informatics Engineering study program. The development process was carried out through the stages of needs analysis, model design, prototype development, trial, and evaluation. The results showed that the ADI laboratory has a high level of validity with an average score of 88.2%, as well as practicality which is considered adequate with a score of 87.4%. In addition, this laboratory was proven effective in improving student learning outcomes, with an average increase of 24% based on pretest and posttest. Pilot tests showed that the system was able to reduce practicum time by 15% compared to physical laboratories, while increasing learning flexibility. This research concludes that ADI labs can be an innovative solution in supporting the digital transformation of higher education. Recommendations for further development include the integration of artificial intelligence technology for learning personalization and cloud-based collaboration features to support teamwork. This virtual laboratory contributes significantly to the creation of an inclusive, flexible and efficient educational ecosystem.